2018
DOI: 10.1192/bjo.2018.24
|View full text |Cite
|
Sign up to set email alerts
|

Long-stay patients with and without intellectual disability in forensic psychiatric settings: comparison of characteristics and needs

Abstract: BackgroundIn recent years, concerns have been raised that too many patients stay for too long in forensic psychiatric services and that this is a particular problem in those with an intellectual disability.AimsTo compare the characteristics, needs, and care pathways of long-stay patients with and without intellectual disability within forensic psychiatric hospital settings in England.MethodFile reviews and questionnaires were completed for all long-stay patients in high secure and a representative sample of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
3
33
2
Order By: Relevance
“…The findings deriving from our sample failed to confirm the observations of Chester et al. ( 30 ) that patients diagnosed with an intellectual disability had significantly shorter stays in forensic institutions, however, conclusions pertaining to this group are limited by a small number of these patients in our sample. There is good evidence to support an association between violence and schizophrenia ( 31 , 32 ), and a systematic review and meta-analysis of 128 studies ( 33 ) found higher rates of inpatient violence in forensic settings compared to acute psychiatric wards in each of 10 countries surveyed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings deriving from our sample failed to confirm the observations of Chester et al. ( 30 ) that patients diagnosed with an intellectual disability had significantly shorter stays in forensic institutions, however, conclusions pertaining to this group are limited by a small number of these patients in our sample. There is good evidence to support an association between violence and schizophrenia ( 31 , 32 ), and a systematic review and meta-analysis of 128 studies ( 33 ) found higher rates of inpatient violence in forensic settings compared to acute psychiatric wards in each of 10 countries surveyed.…”
Section: Discussioncontrasting
confidence: 99%
“…In the one-way analysis of variance from among eight categorical diagnoses based on the ICD-10, schizophrenia and schizoaffective disorder were found to significantly prolong LoS [Kruskal-Wallis Test: H (8, N = 150) = 24.66962 p = .0018], which is consistent with earlier studies (10)(11)(12)(13). The findings deriving from our sample failed to confirm the observations of Chester et al (30) that patients diagnosed with an intellectual disability had significantly shorter stays in forensic institutions, however, conclusions pertaining to this group are limited by a small number of these patients in our sample. There is good evidence to support an association between violence and schizophrenia (31,32), and a systematic review and meta-analysis of 128 studies (33) found higher rates of inpatient violence in forensic settings compared to acute psychiatric wards in each of 10 countries surveyed.…”
Section: Discussionsupporting
confidence: 73%
“…However, inpatient services for people with IDD and mental health or behavioural problems in the UK have come under scrutiny as a result of an abuse scandal which was exposed by an investigative report broadcast on the UK BBC television programme 'Panorama' in 2011, 61 and the model has recently begun to fall out of favour in the UK. 62 The resulting "Transforming Care" programme committed the Department of Health to a rapid reduction in the number of people with IDD within inpatient care, particularly those who were perceived to have been detained for reasons of challenging behaviour. 57 Concerns have been raised about the application of the principles of the Transforming Care programme to those in inpatient secure IDD services.…”
Section: Inpatient Secure Idd Servicesmentioning
confidence: 99%
“…6 The population in inpatient secure IDD services therefore represent a number of challenges to current UK government policy, and clarifications regarding their status is required. 62…”
Section: Inpatient Secure Idd Servicesmentioning
confidence: 99%
See 1 more Smart Citation